Магнитное поле и электродинамические силы трехобмоточного электромагнитного перемешивателя - Карлов, А.Н.; Кондратенко, И.П.; Ращепкин, А.П. (Технічна електродинаміка, 2011)
The calculation method of electromagnetic fields and power parameters of liquid metal three-winding electromagnetic stirrers executed with phase zone 120º windings, in the assumption of the infinite length in an axial direction has been developed. Magnetic field distribution in a cavity of stirrer is defined at an assumption that axial, radial and azimuthally components of liquid metal flow are vanished. Cases of concordant and opposing motion of rotating magnetic field for a circular and two arc-type machines, as well as opposing motion of fields for arc-type machines have been considered.